Image-Based Sexual Abuse and EU Law: A Critical Analysis - Carlotta Rigotti; Clare McGlynn; Franziska Benning (German Law Journal)
In May 2024, the European Union adopted the Directive on violence against women and domestic violence, marking the first EU-wide binding legislation to address various forms of sexualized and gendered harm. This Article provides the first comprehensive analysis of the Directive’s provisions on image-based sexual abuse (“IBSA”), encompassing the non-consensual taking, creating, and sharing of intimate materials, as well as threats to distribute them. While acknowledging the aim to harmonize legislation at the Union level, the Article identifies a range of limitations and the failure to fully reflect the diverse experiences of victims. Additionally, the Article evaluates the complementary roles in combating IBSA of the Digital Services Act and the AI Act which impose obligations on online platforms, search engines, and AI developers. Overall, the current EU framework represents a promising but partial approach. If the EU is to comprehensively address IBSA and safeguard victims’ rights, implementation beyond the minimum will be required together with proactive, effective regulation.